Small and medium-sized enterprises in the EU's sustainability disclosure regime : A result of the tense relationship between the European Green Deal and Capital Markets Union? - Honkanen, Manu (My University, 2023)
The thesis examines the compatibility of the European Union's two flagship initiatives, the European Green Deal and the Capital Markets Union, from the perspective of small and medium-sized enterprises. The compatibility is assessed by looking in particular at the sustainability disclosure regime. The European Green Deal and the expansion of the sustainability reporting obligations are intended to improve corporate responsibility and contribute to the ambitious climate objectives of the European Union. Simultaneously, key objectives of the Capital Markets Union are minimising the regulatory burden on small and medium-sized enterprises, lowering barriers for listing on capital markets and improving their access to finance. As a result of lowering compliance costs for small and medium-sized enterprises, the sustainability disclosure regime is mainly limited to large undertakings, companies listed on regulated markets, and financial market participants. Consequently, the thesis examines whether the scope limitations of sustainability disclosure lead to difficulties in achieving the objectives of the flagship projects. The thesis is theoretically oriented by utilising perspectives of legal-dogmatic and law and economics research as well as regulation theories. The European Union's regulatory strategy on sustainable reporting is reviewed by analysing the European Union's secondary legislation, as well as proposals, opinions and impact assessments of regulatory initiatives from different authorities of the European Union. Furthermore, the evaluation is supported by legal and economic research on the position of small and medium-sized businesses in relation to several legislative approaches for corporate sustainability reporting, as well as research on the conditions for various regulatory strategies. The thesis's key finding is that the European Union's regulatory strategy on sustainability disclosure regime exemplifies the tense relationship between the European Green Deal and the Capital Markets Union, in particular regarding the role of small and medium-sized enterprises. Neglecting statutory reporting obligations for most small and medium-sized enterprises may hinder Europe's green transition objectives. Moreover, the obligation for financial market participants to report on the sustainability of their investment decision-making increases the risk that small and medium-sized companies will continue to struggle to receive funding. To avoid the risks, the thesis proposes an expansion of the scope of the corporate sustainability reporting directive to include companies listed on multilateral trading facilities and a change in regulatory strategy requiring that medium-sized companies operating in high-risk industries report on their sustainability. In addition, the thesis provides a policy adjustment for measures reducing the regulatory burden, emphasizing the need for improved support and information rather than scope restrictions.

Tutkielman tarkoituksena on arvioida Euroopan unionin kahden kärkihankkeen, Euroopan vihreän kehityksen ohjelman ja Pääomamarkkinaunionin, tavoitteiden yhteensopivuutta pienten ja keskisuurten yritysten näkökulmasta. Yhteensopivuutta arvioidaan tarkastelemalla erityisesti vastuullisuusraportointia koskevaa sääntelyä. Euroopan vihreän kehityksen ohjelman ja vastuullisuusraportointisääntelyn tarkoituksena on parantaa yritysten vastuullisuutta ja edistää Euroopan unionin kunnianhimoisia ilmastotavoitteita. Samanaikaisesti Pääomamarkkinaunionin keskeisinä tavoitteina on vähentää pienille ja keskisuurille yrityksille aiheutuvia kustannuksia, alentaa niiden kynnystä listautua säännellyille markkinoille tai muille kauppapaikoille sekä parantaa rahoitusmahdollisuuksia. Sääntelytaakan keventämisen varmistamiseksi, vastuullisuusraportointivelvollisuutta ei ole asetettu pienille ja keskisuurille yrityksille, vaan suurelta osin vain suurille ja säännellyillä markkinoille listatuille yhtiöille sekä finanssimarkkinatoimijoille. Tutkielmassa tarkastellaankin, aiheuttaako vastuullisuusraportointisääntelyn soveltamisalarajaukset ongelmia kärkihankkeiden tavoitteiden saavuttamiselle. Luonteeltaan tutkielma on teoreettinen hyödyntäen näkökulmia oikeusdogmatiikasta, oikeustaloustieteestä ja eri sääntelyteorioista. Euroopan unionin vastuullisuusraportointia koskevaa sääntelystrategiaa arvioidaan tarkastelemalla Euroopan unionin sekundäärilainsäädännön lisäksi eri toimielimien ehdotuksia, lausuntoja ja vaikutusarvioita. Arvioinnissa hyödynnetään myös oikeus- ja taloustieteellisiä tutkimuksia pienten ja keskisuurten yritysten suhtautumisesta vastuullisuusraportointiin ja eri sääntelyvaihtoehtoihin sekä tutkimuksia eri sääntelystrategioiden edellytyksistä. Tutkielman keskeisenä havaintona on, että Euroopan unionin valitsema sääntelystrategia heijastelee Euroopan vihreän kehityksen ohjelman ja Pääomamarkkinaunionin välistä jännitteistä suhdetta pienten ja keskisuurten yritysten osallistamisen suhteen. Ottaen huomioon, että pienet ja keskisuuret yritykset muodostavat yli 99 % Euroopan unionin alueen yrityksistä, niiden jättäminen suurelta osin vastuulllisuusraportointisääntelyn soveltamisalan ulkopuolelle muodostaa riskin, että Euroopan vihreän kehityksen ohjelman tavoitteet jäävät saavuttamatta. Lisäksi, kun finanssimarkkinatoimijat ovat velvollisia raportoimaan omien sijoituspäätöstensä vastuullisuudesta, riski kasvaa, että pienet ja keskisuuret yhtiöt, jotka eivät ole raportointivelvollisuuden piirissä, jäävät vaille pääoma- tai lainarahoitusta. Edellä mainittujen riskien välttämiseksi, tutkielmassa ehdotetaan vastuullisuusraportointidirektiivin soveltamisalan laajentamista monenkeskisissä kaupankäyntijärjestelmissä listattuihin yhtiöihin sekä sääntelystrategian muuttamista niin, että keskisuuret yhtiöt, jotka toimivat riskipitoisilla toimialoilla olisivat myös velvollisia raportoimaan vastuullisuudestaan. Tämän lisäksi tutkielmassa tarjotaan toimintamuutosehdotus sääntelytaakan keventämistapoihin korostaen tuen ja informaation lisäämistä soveltamisalarajoitusten sijaan.
Keywords: European Green Deal, Capital Markets Union, financial markets law, sustainability disclosure, SMEs